Pengaruh Kepemimpinan Transaksional dan Stres Kerja Terhadap Kepuasan Kerja Karyawan PT. Panca Dewata Denpasar, Bali. - Wijaya, I Komang Prawina; Putra, Made Surya (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of transactional leadership and job stress on job satisfaction of employees of PT. Panca Dewata Denpasar, Bali. This study used quantitative research by using surveys and questionnaires to 48 respondents. Obtained findings that simultaneous variable transactional leadership and job stress influence on job satisfaction of employees at PT. Panca Dewata Denpasar, Bali. Other results found that partially can be seen that the variable transactional leadership has a positive effect on job satisfaction of employees at PT. Panca Dewata Denpasar, Bali. Furthermore, it is known that partially variable job stress negatively affects job satisfaction of employees at PT. Panca Dewata Denpasar, Bali. Finally, transactional leadership variables (X1) is the variable that has the most dominant influence on job satisfaction of employees at PT. Panca Dewata Denpasar, Bali.   Keywords : Transactional Leadership, Job Stress, Job Satisfaction
Keywords: Transactional Leadership, Job Stress, Job Satisfaction